Los procesos cognitivos básicos de atención y memoria y la comprensión lectora en estudiantes del primer ciclo de la carrera de Pedagogía de las ciencias experimentales Matemáticas y la Física de la Facultad de Educación, el Arte y la Comunicación de la Universidad Nacional de Loja, 2024. - Gaona Moreno, Jakelin Araceli (2024)
The present research focuses on analyzing the relationship between the Basic Cognitive Processes of Attention and Memory, and the levels of Reading Comprehension in students of the first cycle of the Pedagogy degree of the experimental sciences Mathematics and Physics of the education Faculty, the Art and Communication from the National University of Loja, 2024. The research gets a quantitative, descriptive, correlational and transversal approach, and a non-experimental design. The instruments used include the d2 Test, the RIAS subscale and the instrument to measure reading comprehension in university students (ICLAU), with a sample made up of 31 students. The SPSS program was used for data processing, the correlation between variables was analyzed using Kendall's Tau-b, and Pearson's linear correlation coefficient for the analysis and interpretation of the results. The results indicate that 54.84% of the students reach a medium level in attention and memory, and 54.8% have a medium level in reading comprehension. It is concluded that, between attention and reading comprehension, as well as between memory and reading comprehension, with Kendall's Tau- b values of 242 and 250, respectively, which according to Pearson's linear correlation coefficient indicates a medium positive correlation between the basic cognitive processes, attention and memory with the reading comprehension; therefore, the alternative hypothesis is accepted and the null hypothesis is rejected.